Bahasa Inggris: Bahasa Inggris - Shifa Nur Zakiyah; Wahya Wahya; Hera Meganova Lyra (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2022)
This study aims to describe the kinship relationship between Sundanese and the new Javanese language by using comparative historical linguistic studies. This research is conducting using qualitative and quantitative descriptive methods and lexicostatistical techniques. Lexicostatistics is a language grouping method that is carried out by calculating the percentage of kinship to determine the level of kinship between the languages ​​being compared. The source of the research data came from 200 Swadesh vocabulary lists which is collecting using the listening method with the conversational engagement technique and continued with the recording technique and note-taking technique. The results show that the Sundanese language and the new Javanese language have a kinship relationship. The results of lexicostatistical calculations yield a percentage of 36% which is included in the family language level. The kinship relationship between Sundanese and the new Javanese language is also marked by the presence of (1) identical word pairs such as [bapa], [kəmbaη], [laηit]. (2) Corresponding word pairs produce 7 rules, namely, /h ø/ such as [hatɛ] and [ati] , /b w/ such as [bulan] and [wulan], /a ɔ/ such as [tuma] and [ tumɔ], /u U/ like [suruƞ] and [surUƞ], /r d l/ like [hidőƞ] and [irəƞ], /j d/ like [jalan] and [dalan], /i I/ like [gariƞ] and [garIƞ]. (3) Word pairs that have phonetic similarities, such as [bɛntaη] and [lintaη], [kɔnɛη] and [kuniη]. (4) Word pairs that differ in one phoneme, such as [suku] and [sikil], [jukut] and [sukət].